2009
DOI: 10.1142/s0192415x09007235
|View full text |Cite
|
Sign up to set email alerts
|

The Augmented Anti-Tumor Effects of Antrodia camphorata Co-Fermented with Chinese Medicinal Herb in Human Hepatoma Cells

Abstract: Antrodia camphorata, unique fungal specie, has been used as a folk medicine in Taiwan for many years. The purpose of this study was to compare the extracts from the solid-state culture of A. camphorata co-fermented with Chinese medicinal herb (AC-CF) with two other extracts from fruiting bodies (AC-FB) or solid-state culture (AC-SS), for their anti-tumor effects in human hepatoma HepG2 cells. We measured in vitro cell proliferation, percentage of apoptosis, population distribution of cell cycles, Western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
(32 reference statements)
0
7
0
1
Order By: Relevance
“…29 Therefore, the pretreatment of TCEE might possibly present not only ergosterol-like triterpenoids but also an inhibitor of AmB activated cell-specific survival factors leading to a significant increase in the apoptotic index at a lower AmB concentration. In addition to AmB, the extract of T camphoratus exhibits adjuvant antitumor effects when combining with traditional chemotherapeutic agents, such as mitomycin C, methotrexate, 29 and cisplatin. 30 Furthermore, as reported in the review by Cohen, 7 an increased intracellular calcium concentration by TCEE in cancer cells associated with the formation of AmB aq-pores might be another potential possibility, which leads to the abrupt decrease of the concentration threshold for the increased apoptotic and potentially synergistic effects by AmB that are observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…29 Therefore, the pretreatment of TCEE might possibly present not only ergosterol-like triterpenoids but also an inhibitor of AmB activated cell-specific survival factors leading to a significant increase in the apoptotic index at a lower AmB concentration. In addition to AmB, the extract of T camphoratus exhibits adjuvant antitumor effects when combining with traditional chemotherapeutic agents, such as mitomycin C, methotrexate, 29 and cisplatin. 30 Furthermore, as reported in the review by Cohen, 7 an increased intracellular calcium concentration by TCEE in cancer cells associated with the formation of AmB aq-pores might be another potential possibility, which leads to the abrupt decrease of the concentration threshold for the increased apoptotic and potentially synergistic effects by AmB that are observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Antrodia cinnamomea (AC) is a Taiwanese fungus species that grows in the hollow trunk of the Cinnamomum kanehirai tree. Previous investigations have indicated that AC may suppress tumor formation (12), enhance the immune system (13), inhibit viral activity and protect the liver (14). It is often used in Taiwanese folk medicine.…”
Section: Improving Insulin Resistance With Antrodia Cinnamomea Mycelimentioning
confidence: 99%
“…21,35) Therefore, although in the present study AC-PS did not show any significant anti-tumor effects as AC-FB and AC-SS did, it might have better anti-inflammatory and anti-oxidant effects than AC-FB or AC-SS. It is possible that in some circumstances extracts of A. camphorata with abundant polysaccharides, like our preparation of AC-PS, can exert antiproliferation effects partially through anti-inflammatory and anti-oxidant mechanisms, as has been observed in other studies, 36,37) perhaps not be through the macrophage-mediated mechanism we.…”
Section: Discussionmentioning
confidence: 60%